RESPON PERTUMBUHAN TANAMAN JATI PLUS PERHUTANI UMUR 11 TAHUN TERHADAP INTENSITAS PENJARANGAN DAN TUMPANG SARI (STUDI KASUS DI BKPH BEGAL KPH NGAWI, PERHUTANI JAWA TIMUR) - Muhammad Fadhil Amiruddin Sudomo; Suryo Hardiwinoto; Sapto Indrioko; Budiadi Budiadi; Daryono Prehaten; Aris Wibowo (Jurnal Pemuliaan Tanaman Hutan, 2021)
Thinning is one of silvicultural management actions in maintaining and increasing growth and quality of standing stands. This study aims to determine growth response of selected teak clone to several intensities of thinning and intercropping. The method was a factorial completely randomized block design (RCBD) with thinning intensity (4 levels): 0% (control = A1), 25% (A2), 50% (A3) and 75% (A4) as the main plot, while intercropping (2 levels), as the sub plot. The results showed that the Current Annual Increment (CAI) of diameter at breast height (CAI DBH), volume/tree (CAI vol/tree) and volume/hectare (CAI vol/ha) of stands gave a significant positive response to thinning intensity treatment. CAI DBH one year after thinning were 0.79 cm, 1.47 cm, and 2.46 cm; increased by 32%, 145% and 310% at the thinning intensity of 25%, 50% and 75% when they compared with the control (0.59 cm). CAI vol/ha of stand in the first year, namely 11.88 m/ha, 14.04m3/ha, and 16.78 m3/ha or with an increase of 9%, 29% and 54% respectively at an intensity of 25 %, 50% and 75% compared to the control.